Analisis Perancangan Sistem Informasi Pergudangan di CV. Karya Nugraha - Bagir, Haidar; Putro, Bramantiyo Eko (Universitas Suryakancana, 2018)
Abstractâ€” The existence of inventory in business activities cannot be avoided. One of the main causes is that products cannot be obtained instantly, but it takes times to get. Lack of good information design and lack of communications led to the delivery of raw materials documents in warehouses often hampered because the system manually logs. It became necessary to design new information systems to facilitate all these activities.Warehousing information system is a system that has been computerized with the database. The research phase begins with an analysis of the current system of warehousing conditions. The goal is to identify the needs of the warehousing system. The next stage is system design. The design phase includes Flowmap, Context Diagram, Data Flow Diagram, Entity Relationship Diagram, and database design using software package xampp and MySQL. The database there are six tables namely, data tables of goods, purchase of goods, delivery of goods, purchasing, suppliers and production tables that have been integrated with all the parts in the company. The result is efficient working time and facilitate the user in input or obtain the required data. Non-functional needs should also be available. The need is minimal computer Dual core with minimal windows operating system 2000 with software package xampp, microsoft acsses, mozila firefox and printer and need to be carried out researcher use technology RFId.Â Keywords: Warehousing; database; information Systems.